A novel mutation in GMPPA in siblings with apparent intellectual disability, epilepsy, dysmorphism, and autonomic dysfunction. Issue 8 (2nd June 2017) - Gold, Wendy A.; Sobreira, Nara; Wiame, Elsa; Marbaix, Alexandre; Van Schaftingen, Emile; Franzka, Patricia; Riley, Lisa G.; Worgan, Lisa; Hübner, Christian A.; Christodoulou, John; Adès, Lesley C.
Abstract : GMPPA encodes the GDP‐mannose pyrophosphorylase A protein (GMPPA). The function of GMPPA is not well defined, however it is a homolog of GMPPB which catalyzes the reaction that converts mannose‐1‐phosphate and guanosine‐5′‐triphosphate to GDP‐mannose. Previously, biallelic mutations in GMPPA were reported to cause a disorder characterized by achalasia, alacrima, neurological deficits, and intellectual disability. In this study, we report a female proband with achalasia, alacrima, hypohydrosis, apparent intellectual disability, seizures, microcephaly, esotropia, and craniofacial dysmorphism. Exome sequencing identified a previously unreported homozygous c.853+1G>A variant in GMPPA in the proband and her affected sister. Their unaffected parents were heterozygous, and unaffected brother homozygous wild type for this variant. Lymphoblast cells from the affected sisters showed complete loss of the GMPPA protein by Western blotting, and increased levels of GDP‐mannose in lymphoblasts on high performance liquid chromatography. Based on our findings and the previous report describing patients with an overlapping phenotype, we conclude that this novel variant in GMPPA, identified by exome sequencing in the proband and her affected sister, is the genetic cause of their phenotype and may expand the known phenotype of this recently described glycosylation disorder.